Gaya Komunikasi Kepala Madrasah Terhadap Peningkatan Kinerja Guru Di MTs Al Huda Pangkalan Susu Kabupaten Langkat - Handoko Handoko (CV. Pusdikra Mitra Jaya, 2021)
This study was conducted to determine how the principal's communication style towards improving teacher performance. Mts Al Huda is one of the educational institutions in Langkat district, which is located at Jl. Kurnia village of Sei Siur Kec. Pangkalan Susu Kab. Leave. Based on the grand tour that the researchers conducted, Mts Al Huda was dominated by underprivileged fishermen's children and Mts Al Huda did not charge education, meaning thats education was held free of charge and had a growing number of students from year to year. The research methodology used is a qualitative approach using descriptive methods. This approach is used to study the problem and get a deep meaning about the Communication Style of the Head of Madrasah towards increasing Teacher Performance in Mts Al Huda Kec. Pangkalan Susu Kab. Leave. The results of the study (1) The communication process that occurred in Madrasah Tsanawiyah Al Huda Kec. Pangkalan Susu Kab. Langkat is already running well, Madrasah principals use formal and informal communication. Where formal communication is used by the head of the Madrasah in meetings in the form of two-way communication by expecting opinions and suggestions from the forum in making decisions. (2) The efforts of the head of Madrasah in improving teacher performance at Madrasah Tsanawiyah Al Huda Kec. Pangkalan Susu is by paying attention to the environment, providing motivation so that it makes teachers feel comfortable in carrying out their duties, while maintaining discipline so that good performance from teachers can be realized. (3) communication of the head of Madrasah Tsanawiyah Al Huda Kec. Pangkalan Susu Kab. Tool in improving teacher performance using The Equalitarian Style and The Relinguishing Style. These two styles are interconnected, where the Equalitarian Style has a common ground, meaning that this communication is two-way, everyone is free to express their opinions or suggestions.